2015
DOI: 10.12681/mms.1467
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Habits and Helminth Parasites of Sardine (S. Pilchardus) and Anchovy (E. Encrasicolus) in the Adriatic Sea

Abstract: We examined the stomach contents of two of the most economically and ecologically important small pelagic fish species, the sardine, Sardina pilchardus and the anchovy, Engraulis encrasicolus, obtained monthly from commercial purse-seine catches operating on Croatian fishing grounds during a one-year period (January–December, 2011). Both species generally showed a similar diet, with copepod and decapod larvae as dominant prey groups. The composition of anchovy and sardine stomach contents was not size- or sex-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 48 publications
8
18
1
1
Order By: Relevance
“…The overall stomach content analysis indicated that sardine is an omnivorous planktivore that fed mostly on animal food, most commonly on copepod crustaceans. Those findings were in line with the available recent studies concerning the feeding preferences of sardines in the Adriatic (Tirelli et al, 2006;Zorica et al, 2016), the Mediterranean (Demirhindi, 1961;Server et al, 2005;Costalago and Palomera, 2014;Brosset et al, 2016), and the Atlantic Ocean (Garrido et al, 2008). However, one should take into account that descriptions of the trophic ecology of each population must be studied independently, due to intraspecific variability of the feeding apparatus and diet composition observed among populations living in contrasting environments (Costalago et al, 2015;Rumolo, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The overall stomach content analysis indicated that sardine is an omnivorous planktivore that fed mostly on animal food, most commonly on copepod crustaceans. Those findings were in line with the available recent studies concerning the feeding preferences of sardines in the Adriatic (Tirelli et al, 2006;Zorica et al, 2016), the Mediterranean (Demirhindi, 1961;Server et al, 2005;Costalago and Palomera, 2014;Brosset et al, 2016), and the Atlantic Ocean (Garrido et al, 2008). However, one should take into account that descriptions of the trophic ecology of each population must be studied independently, due to intraspecific variability of the feeding apparatus and diet composition observed among populations living in contrasting environments (Costalago et al, 2015;Rumolo, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, this pattern was linked to the fact that the investigated area in the study by Garrido et al (2008) was described as an upwelling area, where diatom blooms occur in the opposite part of the year (spring-summer season). Hence, the winter increase of diatom prey in this study is in accordance with the phytoplankton annual cycle in the Adriatic Sea, characterized by pronounced Zorica et al (2016).…”
Section: Discussionsupporting
confidence: 86%
“…The overall biological data obtained in this study for the sardines collected by commercial purse seiners in the eastern Adriatic Sea throughout a one-year period (March 2017-February 2018) were consistent with the review by Morello and Arneri (2009) for this Adriatic sardine stock. The length distribution of the sardines investigated was within the ranges obtained for this type of fishing gear operating along the eastern side of the Adriatic, specifically the Croatian fishing grounds (Sinovčić et al 2008, Kraljević et al 2014, and their reproductive traits were consistent with those of previous studies (Brosset et al 2015, Zorica et al 2016, 2017. Females dominated the sardine population investigated in this study, in agreement with previous studies, with the exception of Mustać and Sinovčić (2010), who reported that the sex ratio of the Adriatic sardine favoured males.…”
Section: Biological Parameterssupporting
confidence: 87%
“…Los nematodos son parásitos típicos de peces marinos (Rello et al, 2008) y también se encontraron presentes en la carga parasitaria de S. sagax del Pacífico que fue investigada en el presente estudio; sin embargo, Reed et al (2012) no registraron su presencia en S. sagax de Sudáfrica, cuya ausencia podría estar relacionada con las temporadas de muestreo, asociada a su vez con la sucesión de especies de las cuales se alimentan los organismos. Zorica et al (2015) realizaron un estudio de los hábitos alimenticios y la variación de la carga parasitaria en dos clupeidos, Sardina pilchardus (Walbum, 1792) y Engraulis encrasicolus (Linnaeus, 1758) en el mar Adriático, descubrieron dentro de la carga parasitaria de ambos organismos al digeneo P. merus y al anisakido Hysterothylacium aduncum (Rudolphi, 1802), organismos también presentes en S. sagax. Los autores argumentaron que esta carga parasitaria varía estacionalmente y se relaciona directamente con los hábitos alimenticos de los clupeidos de su estudio.…”
Section: Discussionunclassified